Sonoelastographic evaluation of plantar fascia in patients with plantar fasciitis: A case–control study - Revanth RB; Rajeswari; Deepti Naik; Yashas Ullas L; Suraj HS; Nikhilendra Reddy AVS (Asian Journal of Medical Sciences, 2022)
Background: Plantar fascitis causes heel pain and the thickened fascia has specific morphological features that can be utilized for early diagnosis through sonoelastographic evaluation. Aims and Objectives: This case–control study was conducted to find out the role of sonoelastography in the diagnosis of plantar fasciitis (PF). Materials and Methods: A case–control study was conducted in the department of radiodiagnosis in a teaching medical college. Thirty clinically diagnosed PF patients and thirty controls were recruited based on selection criteria. Shear wave elastography (SWE) was done for all participants and the thickness of plantar fascia and strain ratio was compared between the groups. Plantar fascia thickness (mm) and elasticity (stain ratio) were considered as the primary outcome variable. coGuide software was used for data analysis. Results: The mean age of the cases was 46.73±16.92 years and controls was 47.5±16.1 years. There was no statistical difference observed between cases and controls in age, sex, and body mass index. There was a statistically significant difference in thickness of the plantar fascia (P<0.001) between cases (4.18±0.77 mm) and controls (3.33±0.71 mm). The difference in strain ratio between study groups was statistically significant (P<0.001). The strain ratio had excellent predictive validity with the area under the curve of 0.929 (P<0.001). Data were analyzed using co-Guide software, V.1.03. Conclusion: Ultrasound elastography can detect the thickening of the plantar fascia and strain ratio has excellent predictive validity in predicting PF.